Comportamiento agronómico del cultivo de acelga (Beta vulgaris L) con diferentes abonos orgánicos en la Unidad Educativa Calazacón de Santo Domingo de los Tsáchilas, año 2014 - Cedeño Cedeño, Luis Gabriel (2015)
This research was conducted in Education Unit Calazacón of Santo Domingo de los Tsáchilas, 2014. Located at Km 6.5 Vía Quevedo left margin; belonging to Santo Domingo Canton province of Tsáchilas. Its geographical location is at 655 m., With a geographical location of 0 ° 13'50 "south latitude and 79 ° west longitude 10'40de, research lasted 180 days. Design Randomized Complete Block (DBCA), with seven treatments and four replications. To determine the average resorted to the use of multiple range test Tukey 95% probability. The agronomic performance of chard (Beta vulgaris L.) under different levels of organic fertilizers was determined in plant height (cm); leaf number and leaf length (cm) establishing that treatment 3 (5 kg of humus) was the best parameters to 45.51 cm; 7.42 and 51.07 cm sheets in the indicated variables. The highest level of organic fertilizer in the production of chard (Beta vulgaris L) it was established with 5 kg of vermicompost by high parameters determined in this treatment. In the economic analysis of treatments was established that the higher revenues in treatment 3 (5 kg of Humus) with $ 480.51 was obtained; greater utility with $ 412.92 and better cost benefit with $ 6.11